Meningkatkan Kesehatan Mental Siswa Melalui Peran Pendidikan Seni dalam Pengembangan Emosional dan Psikologis - Nubakti, Kadek Dea Aristha Astriyani (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2025)
Arts education has been recognized as a tool for developing creativity. Still, in recent years, a growing body of research has demonstrated the potential of the arts in supporting students' mental health. This study aimed to explore the effect of arts activities on students' mental health at a high school in Denpasar City, focusing on reducing stress and improving students' emotional well-being. The method used was a quantitative approach with an experimental design, where 50 students involved in arts activities had their stress levels measured before and after participation in fine arts, music, and dance activities. The paired t-test results showed a significant decrease in students' stress levels, with a p-value <0.05. This decrease suggests that arts activities reduce stress and improve students' emotional well-being. This study contributes to developing a more inclusive arts education curriculum, which emphasizes developing creative skills and integrating psychological aspects to support students' mental health. In conclusion, this study underscores the importance of incorporating arts activities in the curriculum to support students' emotional well-being in the school environment.